Geomorphological Map of the Soi Crater Region on Titan. Issue 1 (4th January 2023) - Schoenfeld, A. M.; Solomonidou, A.; Malaska, M. J.; Lopes, R. M. C.; Birch, S. P. D.; Le Mouélic, S.; Florence, M.; Verlander, T.; Wall, S. D.; Elachi, C.
Abstract: We mapped the Soi crater region at 1:800, 000 scale and produced a geomorphological map using methodology presented by Malaska, Lopes, Williams, et al. (2016), https://doi.org/10.1016/j.icarus.2016.02.021 and Schoenfeld et al. (2021), https://doi.org/10.1016/j.icarus.2021.114516 . This region spans longitude 110° to 180°W and latitude 0° to 60°N and is representative of the transition between the equatorial, mid‐latitude, and high‐latitude northern regions of Titan. We used Cassini Synthetic Aperture Radar (SAR) as our primary mapping data set. For areas where SAR was not available, we used lower resolution data from the Imaging Science Subsystem, the Visible and Infrared Mapping Spectrometer, radiometry, and high‐altitude SAR for complete mapping coverage of the region. We identified 22 geomorphological units, 3 of which have been discussed in existing literature but have not yet been incorporated into our mapping investigations. These include sharp‐edged depressions ( bse ), ramparts ( brh ), and bright gradational plains ( pgh ). All six major terrain classes are represented in this region: Craters, Labyrinth, Hummocky/mountainous, Plains, Dunes, and Basin and Lakes. We find that plains dominate the surface of the Soi crater region, comprising ∼73% of the mapped area, followed by dunes (∼14%), mountains/hummocky terrains (∼12%), basin and lakes (∼0.7%), labyrinth terrains (∼0.5%), and crater terrains (∼0.4%). We also observe empty lakes as far south as 40°N. The Soi crater region largely has the same collection and proportion of geomorphological units to other mapped regions on Titan. These results further support the hypothesis that surface processes are, broadly speaking, the same across Titan's middle and equatorial latitudes, with the exception of Xanadu. Plain Language Summary: Titan is the largest moon of Saturn and was studied by the Cassini‐Huygens mission for 13 years. The mission revealed this moon to be a geologically interesting world, with Earth‐like features such as lakes, dunes, rivers, and depositional plains. However, the chemistry of the moon is based on organic molecules at cryogenic temperatures, as opposed to silicate rock and water. We prepare a geomorphology map of a particular region, known as the Soi crater region, in order to classify and catalog the terrain of this region. We use data from Cassini's RADAR, Visible and Infrared Mapping Spectrometer, and Imaging Science Subsystem instruments, but map primarily with Synthetic Aperature Radar. In doing so we make interpretations about the geology of Titan's equatorial and mid‐latitudes areas, which the Soi crater region encompasses. We find that broadly speaking, the Soi crater region follows trends for other equatorial and midlatitude regions of Titan, but do find a few surprises, such as mid‐latitude lake features typically associated with Titan's polar regions. Key Points: Units are described in greater detail as part of the evolving Titan geomorphology mapping schema Empty lakes may reach latitudes as equatorial as 40°N on Titan The Soi crater region is consistent with the narrative of Titan's equatorial and mid‐latitudes being dominated by organic depositional materials